2001
DOI: 10.7547/87507315-91-2-79
|View full text |Cite
|
Sign up to set email alerts
|

Plantar Verrucae in Patients with Human Immunodeficiency Virus

Abstract: Several previous studies have yielded data showing that plantar and other cutaneous verrucae follow a more aggressive course in patients infected with human immunodeficiency virus (HIV) than in uninfected individuals. A pilot study was undertaken to identify trends in a sample population that would support this characterization of plantar verrucae in HIV+ patients and to determine whether there are differences in treatment response between HIV+ and HIV- patients. The results show that the HIV+ patients in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Similar to common warts, immunocompromised patients have been observed to have a significantly greater number of plantar warts as well as longer duration, higher treatment resistance, and greater frequency of recurrence (50,51). King et al (50) have confirmed that HPV2, HP27, and HPV57 can also frequently be detected in plantar warts of HIV-positive patients.…”
Section: Plantar Wartsmentioning
confidence: 98%
“…Similar to common warts, immunocompromised patients have been observed to have a significantly greater number of plantar warts as well as longer duration, higher treatment resistance, and greater frequency of recurrence (50,51). King et al (50) have confirmed that HPV2, HP27, and HPV57 can also frequently be detected in plantar warts of HIV-positive patients.…”
Section: Plantar Wartsmentioning
confidence: 98%
“…Verrucae are found in all age groups, are frequently associated with immunosuppression and late stages of HIV infection, and tend to reoccur following treatment (Barbosa, 1998;Porro et al, 2003;Rodrigues et al, 2001;Whitaker et al, 2001). Improved DNA extraction methodology from thick, keratinized tissue (Herber and Herold, 1998;Pfannenstein et al, 2000;Walsh et al, 1991) and consensus nested or multiplexed PCR (Berkhout et al, 1995;Gravitt and Manos, 1992) have provided means to obtain incidence and prevalence data.…”
Section: Introductionmentioning
confidence: 97%